TRAINING IN THE MANUFACTURE OF ECO-ENZYMES AND ECO-ENZYME SOAP FROM BORNEO’S NATURAL PLANTS FOR STUDENTS OF THE BIOLOGY EDUCATION PROGRAM AT UNIVERSITY OF PALANGKA RAYA - Saritha Kittie Uda; Elga Araina; Shanty Savitri; Akhmadi (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
The Biology Education Study Program at the Faculty of Teacher Training and Education (FKIP) Universitas Palangka Raya (UPR), strives to integrate biological and educational knowledge to produce independent entrepreneurs based on science and technology in community service activities (PKM). Waste management, especially around the UPR campus, is a key focus of research and service, with one solution being the Eco-Enzyme technology from organic waste processing of Borneo plants. This community service activity aims to provide knowledge and skills to students of the Biology Education Study Program FKIP UPR in processing organic waste into economically valuable Eco-Enzymes and Eco-Enzyme Soap. This PKM activity is conducted in collaboration with the Katingan Eco-Enzyme Community Partner to produce superior Eco-Enzyme liquid using three types of sugar and Eco-Enzyme soap branded as Sarithaku. Reflections from participants after attending this training showed that 80% of the participants rated the overall training activities as very good, 86.7% agreed that the training was very beneficial, 73.3% found the training method very effective, 60% noted an increase in their knowledge about Eco-Enzyme, and 70% planned to make their own Eco-Enzyme. This activity is expected to support the reduction of organic waste, increase economic value, and enhance knowledge in biology and environmental sciences.